Ultrasound assessment of subcutaneous adipose tissue in cyclists of different categories - Giorgi, A.; Vicini, M.; Porfido, L.; Martinez-Gonzalez, B. (Journal of Science and Cycling, 2024)
Body composition has a large impact on cycling performance. Successful cyclists aim to maintain body adipose tissue as low as possible. This study seeks to investigate the subcutaneous adipose tissue (SAT) thickness and body fat percentage (BF%) in cyclists of different categories. Thirteen junior cyclists, eighteen U23 cyclists and nineteen professional cyclists underwent B-mode ultrasound assessment of subcutaneous adipose tissue at seven ISAK anatomical sites. Professional riders showed the smallest sum of SAT thickness, ISAK, and BF%, in comparison of the junior and U23 (p< 0.001). The current study provides information of SAT thickness and BF% assessment through ultrasound B-mode in different categories of cyclists.